BASIC WORK SKILL DEVELOPMENTIN THE DISRUPTION ERA FOR UNDERGRADUATE - Sanpipat , Suphakit; Prachyapruit, Apipa (Journal of Educational Review Faculty of Education in MCU, 2025)
This research aims to synthesize concepts related to fundamental work skills in the era of disruption. The sample group consists of HR executives, organizational development officers, and training officers from various agencies and companies. The research instruments include document analysis forms and interview forms, focusing on essential work skills for undergraduate students in this disruptive era. The data is analyzed using frequency analysis and Mayring’s Qualitative Content Analysis method to systematically organize, present, summarize, interpret, and verify the accuracy of the findings. The research results found that: 1) The study of documents on basic work skills in the era of change for graduate students identified 34 basic work skills. The skill with the highest frequency was initiative and creativity skills, followed by analytical thinking skills, adaptability and flexibility skills, stress coping skills, and technology skills. Ranked third were complex problem-solving skills, critical thinking skills, self-management skills, communication skills, teamwork skills, and business skills. 2) The results of interviews with business establishments regarding basic work skills in the era of change for graduate students revealed 19 skills. The most frequently mentioned skill was communication skills, followed by analytical thinking skills and creative thinking skills. In third place were systems thinking skills, teamwork skills, technology skills, and the ability to learn new things and accept change.